R‐ and S‐citalopram concentrations have differential effects on neuropsychiatric scores in elders with dementia and agitation - Ho, Thang (Br J Clin Pharmacol, 2016)
AIMS: The aim was to determine the relationship between (R) and (S)‐citalopram enantiomer exposure (AUC(0,24 h)) and therapeutic response in agitated individuals greater than 60 years old with Alzheimer's dementia (AD). METHODS: Citalopram enantiomer exposures (AUC(0,24 h)) derived from an established population pharmacokinetic analysis were utilized to explore the relationship between (R)‐ and (S)‐citalopram area under the curve (AUC(0,24 )) and Mini‐Mental State Examination (MMSE), Neurobehavioural Rating Scale‐Agitation Subscale (NBRS‐A), modified Alzheimer's Disease Cooperative Study‐Clinical Global Impression of Change (mADCS‐CGIC) and Neuropsychiatric Inventory Agitation subscale (NPIA) scores. Time dependent changes in these scores (disease progression) were accounted for prior to exploring the exposure effect relationship for each enantiomer. These relationships were evaluated using a non‐linear‐mixed effects modelling approach as implemented in nonmem v7.3. RESULTS: (S)‐AUC(0,24 h) and (R)‐AUC(0,24 h) each contributed to improvement in NBRS‐A scores (k3(R) −0.502; k4(S) −0.712) as did time in treatment. However, increasing (R)‐AUC(0,24 h) decreased the probability of patient response (maximum Δ −0.182%/AUC(0,24 h)) based on the CGIC while (S)‐AUC(0,24 h) improved the probability of response (maximum Δ 0.112%/AUC(0,24 h)). (R)‐AUC(0,24 h) was also associated with worsening in MMSE scores (−0.5 points). CONCLUSIONS: Our results suggest that citalopram enantiomers contributed differentially to treatment outcomes. (R)‐citalopram accounted for a greater proportion of the adverse consequences associated with racemic citalopram treatment in patients with AD including a decreased probability of treatment response as measured by the CGIC and a reduction in MMSE scores. The S‐enantiomer was associated with increased probability of response based on the CGIC.